Neurociencias, educación y salud mental - Arboccó de los Heros, Manuel (2015)
The following article presents a series ofinvestigations, reflections, and quotes aboutneuroscience, education, and psychology. Eacharea is specialized in some matters but that atsome point they share territory, and help us tounderstand –increasingly– the complex worldof learning, the brain, and human behavior.We hope to be of interest and promoter of newthoughts.